The influence of hotel restaurant antributes towards customer satisfaction and return intention - Marry Tracy anak Pawan (2016)
The purpose of this study is to assess the influence of hotel restaurant attributes (food quality, service quality, atmosphere, price and value) towards customer satisfaction and return intention towards hotel restaurants. This study also examines the mediating effect of customer satisfaction towards relationship of hotel restaurant attributes (food quality, service quality, atmosphere, price and value) and return intention. Using a quantitative approach, a questionnaire was distributed to respondents who dined in at the hotel restaurants in the Kota Kinabalu. A total of 423 questionnaires were distributed to respondents in selected hotel restaurants in Kota Kinabalu. The selected hotels where data are collected are Promenade Hotel, Grand Borneo Hotel, Hyatt Hotel, Le Meridien Hotel, Courtyard and Novotel. Only 400 questionnaires are useable and were analysed. Meanwhile, data was analyzed using Partial Least Square via Structural Equation Modelling (PLS-SEM). The result showed that the food quality, service quality, atmosphere, price and value have a significant effect to the customer satisfaction. The mediation result showed that customer satisfaction mediates the relationship between food quality, service quality, atmosphere, price and value and return intention. This study assists the hotel industry in Kota Kinabalu generally in obtaining a better picture of key factors that determine customer satisfaction in order to stay competitive with other freestanding restaurant. Besides that, the attributes of price and value are new attributes added to the framework of the hotel restaurant attributes towards customer satisfaction and return intention. Most previous studies only discuss food quality and service quality toward customer satisfaction. Thus, this study makes a contribution the literature focusing on hotel restaurants in Kota Kinabalu, Sabah.